Consultation use of a computer by general practitioners - Harzmark, Guy (1984)
Reporting on an experimental field study of computer use by general practitioners during consultations, this paper focuses particularly on the experiences of the doctors in their efforts to communicate concurrently with a patient and a computer. Through the analysis of logs of computer use, video recordings of consultations and interviews with doctors, the authors report on the uptake of the computer facilities, the impact of such use on information handling during the consultation, the doctors' views about using the system, and finally the relationship between doctors' `natural' consulting styles and their uptake and views of the system.